2013
DOI: 10.1007/s00256-013-1664-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of trochlear dysplasia with degenerative abnormalities in the knee: data from the Osteoarthritis Initiative

Abstract: Objective To evaluate trochlear morphology as a potential risk factor for patellofemoral osteoarthritis, determined by morphological and quantitative measurements of cartilage degeneration using 3T magnetic resonance imaging (MRI) of the knee. Materials and Methods MR images of right knees of 304 randomly selected subjects, aged 45–60 years, from the Osteoarthritis Initiative (OAI) progression cohort were screened for trochlear dysplasia, defined by an abnormal trochlear depth. Out of 304 subjects, n=85 demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 31 publications
2
45
2
1
Order By: Relevance
“…Our data support these observations because lower extremity alignment affected the differences in tibiofemoral cartilage T 1q but not the differences in patellofemoral cartilage T 1q . One anatomic factor that has been shown to be related to patellofemoral OA that we did not evaluate in our study is trochlear dysplasia [28]. Furthermore, it may be possible that the interaction of sex and alignment may be different for medial and lateral patellofemoral compartments, although recent studies have not reported it [23].…”
Section: Discussioncontrasting
confidence: 48%
“…Our data support these observations because lower extremity alignment affected the differences in tibiofemoral cartilage T 1q but not the differences in patellofemoral cartilage T 1q . One anatomic factor that has been shown to be related to patellofemoral OA that we did not evaluate in our study is trochlear dysplasia [28]. Furthermore, it may be possible that the interaction of sex and alignment may be different for medial and lateral patellofemoral compartments, although recent studies have not reported it [23].…”
Section: Discussioncontrasting
confidence: 48%
“…There is new evidence that abnormal structure or alignment of the PFJ may lead to cartilage damage and focal areas of loading and stress manifested as bone marrow lesions (BMLs). Stefanik et al 13 reported that knees in the MOST cohort with patella alta and abnormal trochlea morphology were associated with cartilage damage and BML, with similar findings reported from the Osteoarthritis Initiative cohort 18…”
Section: Section 1: Natural History Of Pfp and Local (Knee Region) Famentioning
confidence: 56%
“…In addition to patellar instability, trochlear morphology has been identified as a potential risk factor for patellofemoral osteoarthritis (Jungmann et al. ) that can be treated by patellofemoral arthroplasty in a middle‐aged patient and by total knee arthroplasty (TKA) in the elderly (Ackroyd et al. ).…”
Section: Discussionmentioning
confidence: 99%